Drivers of behaviors: How do city pilots shape residential energy-related emissions through perceptions? - Xing, Hua; Li, Xiangyang (Frontiers in Psychology, 2023)
Residential energy consumption, as a major source of emissions in cities, is also a policy priority for the construction of low-carbon cities. Occurrence of residential energy saving and emission mitigation behaviors is closely related to low-carbon perceptions. In order to lower energy consumption emissions, cities need to shape residential low-carbon perceptions. This study takes low-carbon city pilots (LCCP) as the policy context and establishes the DID model to investigate residential energy emissions in Chinese prefecture-level cities. Planned behavior theory is utilized to analyze the influence mechanism of residential low-carbon perceptions. Research findings: (1) LCCP can decrease residential energy consumption emissions and pass a variety of robustness tests. Multiple pilot eligibility and policy lags would reinforce policy effects. (2) Mechanism analysis shows that LCCP can strengthen residential behavioral attitudes, establish subjective norms, and adjust perceived behavioral control. All three mechanisms together shape residential low-carbon perceptions, which consequently promote energy emission mitigation behaviors. (3) Due to differences in geographic location and city size, there is heterogeneity for LCCP. Therefore, this study further proposes policy recommendations contributing to lowering residential energy consumption emissions: intensify residential emission mitigation policies, enhance residential low-carbon perceptions, and incorporate local characteristics.